Evaluating tourism development models for Bodrum peninsula in Turkey - Gezici, F.; Gul, A. Y.; Alkay, E. (WIT PRESS, 2006)
Significant destination areas in Mediterranean countries have faced the problems of mass tourism near the coastal areas and as a declining process. In addition, planning coastal regions, alternative tourism approaches and increasing quality have become the main strategies for the solutions. The development process of tourism in the Bodrum peninsula as one of the significant coastal destinations in Turkey contains certain threats on the sustainability of tourism. Misleading marketing, overcoming thresholds of development in the peninsula and encouraging construction along the coast impose threats for the future of tourism in Bodrum. In this paper, the impacts of tourism on different dimensions such as the identity of the region, the natural-cultural environment, its social and economic structure and the factors that constitute a threat for the sustainability of tourism in Bodrum will be discussed. Secondly, the principal component analysis is applied in order to put forward the impact of defined variables on development in Bodrum. Different components are discussed for the evaluation of different development models related to impact of the variables. The results point out the threats on natural and cultural values and identity, and further on the deficient contribution to the local economy.
Keywords: tourism; development; principal component analysis; Bodrum peninsula; Environmental Sciences & Ecology; Sociology; Transportation